Faith in Flux: A Narrative Approach to Transformational Curriculum Management in Christian Education Amidst Digital Disruption - Berdinata Massang; Hotliong Verawaty; Juanda Manullang (Yayasan Adra Karima Hubbi, 2026)
Background: Global disruption and the acceleration of digitalization have significantly transformed the educational landscape, including Christian education, which has traditionally managed its curriculum in an administrative and procedural manner. This condition poses serious challenges to the relevance of the curriculum in addressing the demands of twenty-first-century competencies while simultaneously maintaining Christian faith values. Purpose: This study aims to analyze the limitations of the administrative curriculum management model in Christian education and to formulate a transformational curriculum management model that is responsive to global disruption and the digitalization of education. Method: The research employs a qualitative approach using a literature review method and conceptual analysis of relevant international and national scholarly works. Results: The findings indicate that a transformational curriculum management model is capable of holistically integrating digital innovation, visionary leadership, and Christian values within the processes of curriculum planning, implementation, and evaluation. The discussion underscores the importance of shifting the curriculum management paradigm from an administrative function toward a strategic and adaptive function. Conclusion: This study concludes that the transformational model represents a relevant and sustainable approach for the development of Christian education in the era of global disruption.